ANALISIS PUTUSAN PENGADILAN NEGERI SEMARANG NO.2/PDT.SUS-PAILIT/2020/PN.SMG MENGENAI PERMOHONAN PEMBATALAN HOMOLOGASI - Khasanah, Nur; Yulistyowati, Efi; Abib, Agus Saiful (Fakultas Hukum, Universitas Semarang, 2022)
ABSTRACT Homologation is the ratification of reconciliation by the judge on the agreement between the debtor and creditor to end bankruptcy. Bankruptcy is one way to resolve debt disputes that smother a debtor, where the debtor no longer has the ability to pay his debts to his creditors. One of the bankruptcy decisions that will be studied in this research is the Semarang District Court Decision Number 2/Pdt.sus-Pailit/2020/PN.Smg. Regarding the request for cancellation of homologation, by discussing the problem of analyzing the judge's consideration in the decision of the Semarang District Court No.2/Pdt.Sus-Pailit/2020/PN.Smg regarding the Request for Cancellation of Homologation and its legal consequences. Based on this, the type of this research is normative juridical with a case approach, the research specification is descriptive and analytical. The data used is secondary data, which is taken by means of literature study and documentation study. The data is then analyzed qualitatively. From the results of this study, it can be concluded that the consideration of the Panel of Judges to grant the Petitioner's request in the Decision of the Semarang District Court No.13/Pdt.Sus-PKPU/2018.PN.Smg is correct because the Respondent was proven negligent/default in fulfilling the contents of the Homologation agreement agreed between PT.BMI TBK and PT.TS in their arrangement there are achievements that must be fulfilled by PT.TS, namely the payment of debt of 82% (eighty two percent) of the total principal debt of the Respondent to the Petitioner or the equivalent of Rp.106,604,576,766, - (one hundred six billion six hundred four million five hundred seventy six thousand seven hundred and sixty six Rupiah) no later than 6 (six months) from the date of the Homologation Decision This is in accordance with the contents of Article 170 paragraph (1) of Law No. 37 of 2004. Legal consequences from the Semarang District Court Decision No.2/Pdt.Sus-Pailit/2020/PN.Smg PT.TS must be Bankrupt with all the legal consequences this is in accordance with Article 291 paragraph (2) of the Bankruptcy Law and PKPU. Keywords : Decision, Court, Cancellation, Homologation.